2022
DOI: 10.1111/ejh.13848
|View full text |Cite
|
Sign up to set email alerts
|

Changes in body mass index during treatment of childhood acute lymphoblastic leukemia with the Nordic ALL2008 protocol

Abstract: Objectives Children with acute lymphoblastic leukemia (ALL) have a tendency to gain weight during treatment. As overweight and obesity associate with health problems, prophylactic interventions are warranted. Therefore, it is important to identify the children most prone to gain weight. Methods Patients aged 2.0–17.9 years at ALL diagnosis were identified from the NOPHO ALL2008 registry. Registry data was complemented with height and weight at the end of therapy from questionnaires. Body mass index (BMI) was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Importantly, an abnormally high BMI z -score at the end of induction was more prevalent among small children aged 0–5 years in our study compared to older patients. Similarly to our research, other studies revealed that younger children, particularly those with a healthy or lower BMI at diagnosis, were most likely to gain weight during treatment [ 28 , 29 ]. Another study performed a univariate logistic regression analysis that revealed younger age to be a risk factor for an increase in BMI standard deviation after induction chemotherapy [ 30 ].…”
Section: Discussionsupporting
confidence: 88%
“…Importantly, an abnormally high BMI z -score at the end of induction was more prevalent among small children aged 0–5 years in our study compared to older patients. Similarly to our research, other studies revealed that younger children, particularly those with a healthy or lower BMI at diagnosis, were most likely to gain weight during treatment [ 28 , 29 ]. Another study performed a univariate logistic regression analysis that revealed younger age to be a risk factor for an increase in BMI standard deviation after induction chemotherapy [ 30 ].…”
Section: Discussionsupporting
confidence: 88%
“…The literature presents an ongoing debate regarding differences between ALL vs. non-ALL patients in the V d and Cl of gentamicin. Given the increased body fat composition in ALL patients ( Egnell et al, 2022 ), some differences in central and peripheral V d can be anticipated when comparing ALL to non-ALL patients. Similarly, disturbances in lean body mass and renal function associated with cytotoxic medication lead to changes in serum creatinine and Cl cr ( Aapro and Launay-Vacher, 2012 , Mach et al, 2022 ), consequently affecting gentamicin clearance ( Ho et al, 1995 ).…”
Section: Discussionmentioning
confidence: 99%
“…Weight gain can be a common side effect of therapies, especially chemotherapy, as well as hormonal therapies used for some cancers, including breast cancer, prostate cancer, and leukemia. [125][126][127] Up to 35% of cancer survivors have obesity, and obesity has been found to increase the risk of death for all cancers combined, with patients who have severe obesity experiencing a >50% increased risk of death than patients with cancer who have a healthy weight. 128 Cancer survivors may have poorer quality diets that may reflect long-term dietary patterns before diagnosis or because changes in taste and other physical and quality-of-life factors affect dietary intake postdiagnosis.…”
Section: Translation To Practice: Exercise and Physical Activity (Nei...mentioning
confidence: 99%
“…Weight‐control considerations differ between cancer survivors and individuals without cancer and may require personalized guidelines. Weight gain can be a common side effect of therapies, especially chemotherapy, as well as hormonal therapies used for some cancers, including breast cancer, prostate cancer, and leukemia 125–127 . Up to 35% of cancer survivors have obesity, and obesity has been found to increase the risk of death for all cancers combined, with patients who have severe obesity experiencing a >50% increased risk of death than patients with cancer who have a healthy weight 128 .…”
Section: Moving Energy Balance Research Toward Clinical Practice Changementioning
confidence: 99%